UJI IDENTIFIKASI BAKTERI Esherichia coli PADA JAMU GENDONG KUNYIT ASEM DI KABUPATEN TEGAL - Inur Tivani; Wilda Amananti; Ahmad Sunardi (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Based on the results of previous studies conducted by researchers in January 2018 showed that the Total Plate Count (ALT) of Jamu Gendong in several villages in Talang sub-district did not meet the quality safety standards (ALT value of more than 104). The high ALT value indicates the presence of bacteria contained in the tamarind tamarind herbal medicine. One of the bacteria that often contaminates food and beverages or drugs is Escherichia coli. E. coli bacteria is a characteristic bacterium contaminated with food or drug samples. The purpose of this study is to test for the presence or absence of E coli bacteria in gedong kunyit asem herbal medicine in Tegal district.The identification test of E. coli bacteria was carried out through two techniques, namely staining and bacterial culture techniques. For coloring techniques, gram coloring tests will be carried out, while bacterial cultures include blood agar plates, and Macconkey agar media.The results showed that gram staining, as well as culture in the media of Blood Agar Plate and Macconkey Agar showed the presence of E. coli bacteria in samples of tamarind ancient tamarind in several villages in Tegal RegencyKeywords: identification test, Escherichia coli bacteria, Jamu genndong, Kunyit asem.